2011
DOI: 10.5009/gnl.2011.5.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management for Giant liver Hemangiomas Greater Than 20 cm in Size

Abstract: Background/AimsThe aim of this study was to investigate the primary management experience for giant liver hemangiomas greater than 20 cm in size.MethodsRecords of patients referred for evaluation of radiologically and/or histopathologically proven giant liver hemangiomas between January 2007 and March 2010 were retrospectively analyzed. The reasons for referral, results of imaging studies, preoperative and surgical treatments, and outcome were reviewed.ResultsA retrospective analysis was performed for 14 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 14 publications
2
38
1
2
Order By: Relevance
“…[3] In study done by Sharma et al, mean age was 40 years. [5] Similar findings were also observed in study done by Rajak et al, in which average age was 35 years. [6] In our study out of 25 cases of amoebic liver abscess 18 (72%) cases were from rural area (Table 4), which is in accordance with study done by Mathur et al [2] In our study 5 (20%) cases of amoebic liver abscess were alcoholic (Table 5), which is in contrast to study done by Mathur et a1 and Seeto et al, in which 70% and 43% cases were alcoholic.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[3] In study done by Sharma et al, mean age was 40 years. [5] Similar findings were also observed in study done by Rajak et al, in which average age was 35 years. [6] In our study out of 25 cases of amoebic liver abscess 18 (72%) cases were from rural area (Table 4), which is in accordance with study done by Mathur et al [2] In our study 5 (20%) cases of amoebic liver abscess were alcoholic (Table 5), which is in contrast to study done by Mathur et a1 and Seeto et al, in which 70% and 43% cases were alcoholic.…”
Section: Discussionsupporting
confidence: 80%
“…[3] In our study USG findings showed hypoechoic lesion in all cases, hepatomegaly in 11 (44%) cases, right lobe was involved in 22 (88%) cases, left lobe in 2 (8%) cases, both lobes in 1 (4%) case, single lesion in 21 (81%) cases and multiple lesion in 4 (16%) cases of amoebic liver abscess. Similar findings were observed in study done by Seeto et al, Mathur et al and Sharma et al [2][3] [5] In our study USG guided aspiration was done in 14 cases of amoebic liver abscess, out of which 10 (52.6%) cases demonstrated tropozoite of E.histolytica on microscopy which is in contrast to study done by Haque et al and Seeto et al in which tropozoite were demonstrated in 11% and 4% cases respectively. [3][8]…”
Section: Discussioncontrasting
confidence: 56%
“…[9][10][11] The incidence of hemangiomas varies from 0.4% to 20%. [1][2][3]6 Hemangioma are often seen between the ages of 30 and 50 years and 5 to 6 times more often in women than in men. 4,6,7,9,10 Therefore, it has been suggested that there may be a relationship between the disease and the use of exogenous steroids or female-specific hormones, although the relationship has not been clearly shown.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7,9,10 Therefore, it has been suggested that there may be a relationship between the disease and the use of exogenous steroids or female-specific hormones, although the relationship has not been clearly shown. 2,3,10 Because most hepatic hemangioma are asymptomatic, they are often recognized incidentally during radiologic tests for other reasons. However, in some patients the location and size of the lesion can cause various signs and findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation